Perbandingan Perbedaan Postur Tubuh Penari pada Pengenalan Gerakan Tari Sigeh Penguten Menggunkan Hidden Markov Model - Yuthsi Aprilinda; Destri Silvira Ocha Eryani; Maria Shusanti Febrianti; Fenty Ariani; Freddy Nur Affandi (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2022)
The Sigeh Penguten dance is a dance originating from Lampung where the Sigeh Penguten dance is often called the worship dance. Traditional dance is one of the heritages of Indonesia culture. This Sigeh Penguten Dance research aims to get comparison results from the data training that has been carried out and to get the desired results in accordance with the data testing that has been carried out. With the advancement of technology, a system is needed to determine the comparison results of training data and a learning system is needed to conduct test data. Where MongoDB is used as a Database to store large files with a better level of security. The training data will be automatically saved to mongoDB in the form of a CSV file. Researchers used 3 phrases, namely Ngerujung, Cockfighting, and Rejecting Cliffs. The system will implement by using a Kinect sensor to detect motion in dance. To get the results, the dancer will stand in front of the Kinet sensor.